Analisis Deskriptif Mengenai Pendapatan dan Pengeluaran Publik dalam Kebijakan Fiskal - Ahmad Fuadi; Raju Adha; Patma Wati; Isnaini Harahap (Universitas Muhammadiyah Surabaya, 2023)
AbstractThis study aims to provide a simple understanding of the concepts of fiscal policy, public revenue, and public spending. In this context, an understanding of fiscal policy is important to understand how the government manages the economy and meets people's needs. Public revenue is a source of funds used by the government to run various programs and public services, such as infrastructure, education, health and social welfare. Public spending includes the allocation of funds for these purposes. The method used is descriptive method. The results of this study are expected to have a strong basic understanding of the role and importance of fiscal policy in regulating the economy and meeting people's needs.Keywords: Fiscal Policy, Income, Public Spending